1998
DOI: 10.2105/ajph.88.12.1787
|View full text |Cite
|
Sign up to set email alerts
|

Residential magnetic fields and childhood leukemia: a meta-analysis.

Abstract: OBJECTIVES: This article uses meta-analysis methodology to examine the statistical consistency and importance of random variation among results of epidemiologic studies of residential magnetic field exposure and childhood leukemia. METHODS: A variety of meta-analytic statistical methods were applied to all available studies combined and on sub-groups of studies chosen by exposure characteristics. Sample sizes and fail-safe n's were calculated to determine the robustness of results and the potential role of pub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2001
2001
2015
2015

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(16 citation statements)
references
References 44 publications
0
16
0
Order By: Relevance
“…Likewise, a meta-analysis in 1998 reported a weak elevated risk of leukaemia for children exposed to residential magnetic fields and a positive association between childhood leukaemia and calculated historic fields ≥0.2 μT (OR = 1.90, 95% CI: 1.07-3.39) (Wartenberg, 1998). However, Tynes and Haldorsen (1997) failed to reproduce such findings, presenting no association between childhood cancer, including leukaemia, and residences near power lines, based on calculations from power line distance and records of load.…”
Section: Field Measurement Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Likewise, a meta-analysis in 1998 reported a weak elevated risk of leukaemia for children exposed to residential magnetic fields and a positive association between childhood leukaemia and calculated historic fields ≥0.2 μT (OR = 1.90, 95% CI: 1.07-3.39) (Wartenberg, 1998). However, Tynes and Haldorsen (1997) failed to reproduce such findings, presenting no association between childhood cancer, including leukaemia, and residences near power lines, based on calculations from power line distance and records of load.…”
Section: Field Measurement Studiesmentioning
confidence: 99%
“…In addition, a meta-analysis of childhood brain tumour studies has also indicated a non-statistically significant link when presenting risk estimates with multiple exposure assessment methods (Wartenberg, 1998). The majority of casecontrol studies however, have failed to provide evidence of a positive association when assessing exposure with a range of methods (Feychting & Ahlbom, 1993;Gurney et al, 1996;Tynes & Haldorsen, 1997;UK Childhood Cancer Study Investigators, 1999), meta-analysis (Mezei et al, 2008) or in conjunction with appliance use either directly by the child or the mother during gestation Preston-Martin et al, 1996).…”
Section: Brain Cancermentioning
confidence: 99%
“…Most suggested increased risk associated to higher exposure, although, in general, 95% Confidence Intervals had null risk in� cluded 41,53,54,55,56,57 .…”
Section: Childhood Leukemiamentioning
confidence: 99%
“…Most subsequent studies have confirmed elevated risks of leukemia [4][5][6], and several meta-analyses have shown significantly elevated odds ratios (ORs) whether exposure was determined through use of wire codes or measured magnetic fields [7][8][9]. In addition there is evidence that leukemia is elevated in adults employed in occupations that involve elevated exposure to EMFs from electricity [10].…”
Section: Health Effects Of Elf Emfsmentioning
confidence: 99%